2010
DOI: 10.1007/s11434-010-3169-5
|View full text |Cite
|
Sign up to set email alerts
|

The permeability effect of microcystin-RR on Escherichia coli and Bacillus subtilis

Abstract: Microcystins are a kind of cyclic hepatoxins produced by many species of cyanobacteria. Most previous work have been done on the toxic effects of microcystins on animals and plants. However, the reports about the effect of microcystins on microbial cells are very limited. In this work, the permeability of MC-RR on the cell outer membrane of Escherichia coli (E. coli) and Bacillus subtilis (B. subtilis) was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that microcystin-RR generates oxidative and cell envelope stress in E . coli [ 26 , 27 , 58 ]. Based on these reports, we hypothesized that exposure to microcystin would trigger differential expression in genes that respond to oxidative and cell envelope stress and that metabolite concentrations would alter as cells respond to induced stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that microcystin-RR generates oxidative and cell envelope stress in E . coli [ 26 , 27 , 58 ]. Based on these reports, we hypothesized that exposure to microcystin would trigger differential expression in genes that respond to oxidative and cell envelope stress and that metabolite concentrations would alter as cells respond to induced stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that microcystins cross animal cell membranes through the transmembrane solute carriers transport family OAPT (Organic Anion Polypeptide Transporters) (Hagenbuch & Meier, 2004;Fischer et al, 2005). Regarding bacteria, it has been shown that microcystins can permeate the membranes of both gram-negative and grampositive bacteria (Dixon et al, 2004;Yang et al, 2010). Therefore, we can presume that MCs might enter bacterial cells and provoke cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…The capability of MCs to penetrate the cell membranes of both gram-negative and gram-positive bacteria was reported by Yang et al [ 72 ], where exposure of Escherichia coli and Bacillus subtilis (isolated and purified from cyanobacterial blooms in Lake Dianchi, China) to MC-RR promoted the bacteriolytic activity of lysozyme through the increased permeability of the cellular outer membrane. The study by Miguéns and Valério [ 73 ] further indicated that different variants of MCs (MC-LR, MC-RR and MC-YR) at various concentrations (1, 10 and 1000 nM) significantly reduced the growth of heterotrophic bacteria (phyla: Firmicutes, Actinobacteria, Bacteroidetes, β-Proteobacteria and γ-Proteobacteria), which were isolated from both cyanobacteria contaminated and non-contaminated Portuguese freshwater reservoirs.…”
Section: Cyanotoxins and Interspecies Interplaymentioning
confidence: 91%